Personal branding - a must have for future corporate leaders / Syed Mohammed Alhady Syed Ahmad Alhady...[et al.] - Syed Ahmad Alhady, Syed Mohammed Alhady; Zakaria, Azfahanee; Zakaria, Zaherawati; Wan Omar, Maznah (2010)
Academicians talk and discuss on Personal Branding with fellow students all the time on the importance of Personal Branding. However some students are just too skeptical to agree and follow the path and used the information which has been given to them. Many students are unaware that personal branding does not happen overnight. It takes quite a while for a person to have a personal brand which would suit a person and does not look fake on him or her. This paper discusses the importance of personal branding for all future corporate leaders and how it would assist them to succeed in the working world.